Electrical and mechanical properties of Sm2O3 doped Y-TZP electrolyte ceramics. Issue 14 (1st October 2018) - Cheng, Jihai; Tian, Changan; Yang, Jie; He, Jianbo
Abstract: This study aimed to investigate the effects of Sm2 O3 dopant on the sintering behavior, electrical and mechanical properties of the sintered Y-TZP ceramic samples. X-ray diffraction (XRD) results show that Sm2 O3 could be dissolved in Y-TZP to form Sm2 O3 and Y2 O3 co-doped t-ZrO2 (SY-TZP). The additions of Sm2 O3 (0.5–3 mol%) to Y-TZP does not affect its phase structure, and the SY-TZP sintered samples maintain a stable tetragonal structure. According to the scanning electron microscopy (SEM) results, it is found that the addition of Sm2 O3 can promote the sintering densification with a uniform grain growth, and dense (> 98% of theoretical) electrolyte ceramics with grain size of 10 µm were obtained after sintering at 1550 °C. Electrical and mechanical properties testing results indicate that the mechanical properties of Y-TZP are not significantly changed by a small amount of Sm2 O3 (0.5 mol%), but the conductivity was improved obviously. The conductivity of 0.5 mol% Sm2 O3 doped Y-TZP (0.5SY-TZP) is 0.02 S cm −1, and the activation energy is 1.012 eV at 800 °C. When the doping amount is more than 1%, the mechanical properties of Y-TZP changes. With the increase of Sm2 O3 content, the hardness and flexural strength of sintered ceramics are reduced, but the conductivity increased. 3SY-TZP sample which sintered at 1550 °C for 4 h shows the highest conductivity, the conductivity and activation energy reaches to 0.026 S cm −1 and 0.863 eV at 800 °C, respectively. Overall, sintering behavior and electrical properties analysis results suggest that Sm2 O3 could be used not only as an effective sintering aid but also can as co-dopant on the optimization of electrical properties for yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) electrolytes.